Examining the socioeconomic outcomes of transport interventions in the Global South - Caulfield, Brian (My University, 2022)
This paper addresses a recurrent distributive issue of transport interventions and aims to develop a framework of an impact evaluation of transport projects particularly tailored to the Brazilian context. The methodology draws upon the literature to employ a quasi-experimental approach performed by means of a difference in difference matching (DIDM) technique. This technique is then applied to a case study in Northeast Brazil, in which the social impacts of a large transport project are analysed. Whilst many transport infrastructure projects have been advertised as key investments to promote regional economic growth, the results show that positive socioeconomic effects arising from these investments may not be captured by the least advantage groups of society. Findings subscribe to the view that transport infrastructure investments broadly contribute to the reduction of multidimensional poverty. This conclusion is particularly illustrated in this case study by the greater positive impacts in eleven socioeconomic indicators of the municipalities on the region of this transport project.
PUBLISHED
Keywords: Transport equity; Global South; Evaluations; Smart & Sustainable Planet; Transport; Policy; Poverty; Transport